U C Berkeley Heavy Reunion at Holiday Inn San Francisco - Watkins, Howard::::::::: (1981)
Front row: Steven "Elmo" Rau, Howard Watkins, Christine Watkins, Jerry Neary, Jane Gumpert, Carol Rau , David Morse, David Atkinson 2nd row: Joe Barkett, Bonnie Neary, Alan Pricco, Theresa Pricco, (Bill Geary's Date), Marsha Ellis Back row: Kirk Wilson, Sally Connell, Cathy Barkett, Denise Morse, Kathy Moniz, Frank Gumpert, Steve Ellis, Bill Geary